A pan-cancer analysis of the prognostic and immunological roles of zinc finger protein 514 in human tumors - Zhao, Shuai; Cheng, Lin; Ji, Xingzhao; Sun, Shengnan; Liu, Yi; Wan, Qiang (Frontiers in Oncology, 2025)
BackgroundRecent studies have highlighted the essential role of the zinc finger gene family, whose encoded proteins play a pivotal role in all stages of tumor initiation and development. Zinc Finger Protein 514 (ZNF514) is a member of the ZNF family, and its abnormal expression and prognostic value in human pan-cancer have not yet been described. The purpose of this study is to investigate the prognostic and immunological roles of ZNF514 in pan-cancer and to confirm its cancer-promoting effect in renal clear cell carcinoma.MethodsIn our study, we utilized the Human Protein Atlas (HPA) database to determine the expression of ZNF514 in human normal and tumor tissues. We also used the Tumor Immune Estimation Resource 2.0 (TIMER 2.0) database to investigate the association between ZNF514 expression and immune checkpoint genes and immune infiltration. To detect the expression and prognostic value of ZNF514 in pan-cancers, we utilized The Cancer Genome Atlas (TCGA) or the Genotype-Tissue Expression (GTEx) databases and analyzed the data using the Kaplan-Meier plotter, GEPIA2, cBioPortal, or Xiantao software. Additionally, we obtained the protein-protein interaction network of ZNF514 from the STRING database. To validate our findings, we performed immunohistochemistry on clinical samples. Furthermore, we conducted cellular functional experiments to examine the effects of ZNF514 overexpression or knockdown on renal clear cell carcinoma cell proliferation, migration, and invasion.ResultsOur study found that ZNF514 expression was elevated in tumor tissues than in normal tissues in most tumor types. Furthermore, high expression of ZNF514 was associated with poor overall survival (OS) and disease-free survival (DFS) in certain tumor types. Further analysis of ZNF514 gene mutation data revealed that ZNF514 protein is infrequently mutated in human cancers. Moreover, ZNF514 affected prognosis and was associated with the expression of multiple immune checkpoint genes and the abundance of tumor-infiltrating immune cells across multiple types of cancer. Finally, our molecular biology experiments confirmed the oncogenic effect of ZNF514 in renal clear cell carcinoma.ConclusionOur study revealed that ZNF514 may serve as an immunological and prognostic biomarker in multiple human cancers, especially in KIRC, LIHC, LUSC, and COAD.